EKOKRITISISME LAWRENCE BUELL: REPRESENTASI ALAM DALAM NOVEL LASKAR PELANGI - Nurul Annisa Putri; Nur Laila Sari; Ratu Cahaya Islami; Nita Widiati (Hiski Malang, 2025)
Nature is a complex system that provides various resources for the survival of all living things. Technological advances have encouraged the massive exploitation of natural resources which has caused various environmental damages and problems. This study aims to describe the representation of nature as a meaningful place and the role of nature in shaping the character's identity in the novel Laskar Pelangi by Andrea Hirata. This research uses a literary ecology approach with a qualitative descriptive method. The data in this study were obtained through literature study method in the form of narration and dialog that shows the representation of nature as a meaningful place and the role of nature in shaping the character's identity in the novel Laskar Pelangi by Andrea Hirata. From the results of the study, it was found that in the novel Laskar Pelangi by Andrea Hirata there is a representation of nature as a meaningful place shown by 6 data and the role of nature in shaping the character identity of the characters shown by 6 data.